Professions de foi ibādites, contribution à l'étude de l'ibādisme et de sa théologie III - Cuperly, Pierre (Université de Paris 4, 1982)
Keywords: Foi -- Traité

Professions de foi ibādites, contribution à l'étude de l'ibādisme et de sa théologie II - Cuperly, Pierre (Université de Paris 4, 1982)
Keywords: Foi -- Traité

Professions de foi ibādites, contribution à l'étude de l'ibādisme et de sa théologie I - Cuperly, Pierre (Université de Paris 4, 1982)
Keywords: Foi -- Traité

ʿAqīdat Abī Sahl Yaḥyà/La ʿAqīda d’Abū Sahl Yaḥyà - Cuperly, Pierre (Cahiers de Tunisie, 1983)
Edition and translation. Arabic text pp. 41-47, an introduction (much the same as Cuperly 1979, 67-74); text of the ʿAqīda: pp. 48-69, 55-84; French translation of the ʿAqīda: pp. 70-94, 85-119.
Keywords: Foi -- Traité

ʿAqīdat Abī Sahl Yaḥyà/La ʿAqīda d’Abū Sahl Yaḥyà - Cuperly, Pierre (Cahiers de Tunisie, 1982)
Edition and translation. Arabic text pp. 41-47, an introduction (much the same as Cuperly 1979, 67-74); text of the ʿAqīda: pp. 48-69, 55-84; French translation of the ʿAqīda: pp. 70-94, 85-119.
Keywords: Foi -- Traité

Introduction à l'étude de l'ibādisme et de sa théologie - Cuperly, Pierre (Office des publications universitaires, 1984)
Keywords: Foi -- Traité

Une profession de foi ibāḍite: la profession de foi d’Abū Zakariyyā’ Yaḥyà Ibn al-Khayr Ibn Abī l-Khayr al-Jannāwunī / ﻋﻘﻴﺪﺓ ﺍﻟﺘﻮﺣﻴﺪ ﻷﺑﻲ ﺯﻛﺮﻳﹼﺎﺀ ﻳﺤﻴﻰ ﺍﻟﺠﻨﹼﺎﻭﻧﻲ ﻭﻫﻲ ﺍﻟﺘﻲ ﻳﺴﻤﹼﻮﻧﻬﺎ ﻋﻘﻴﺪﺓ ﻧﻔﻮﺳﺔ - Cuperly, Pierre (Bulletin d'Études Orientales, 1981)
Pp. 48-54 the full Arabic text of the ʿAqīdat al-Tawḥīd (ʿAqīdat Nafūsa), based on an edition at the beginning of a collection published in 1325/1907-8 (56 pp., 18x13 cm.). Cuperly discusses the subjects treated in the ʿAqīda (listed on p. 24-25), making a comparison i.a. with the Muqaddimat al-Tawḥīd of Abū Ḥafṣ ʿUmar b. Jamīʿ.
Keywords: Foi -- Traité; Jannāwunī, Yaḥyā b. al-Khayr

تحليل ما يتعلق بأصول الدين من التراث الإباضي بالمغرب في القرون التالية : 10-11-12 هـ/16-17-18 م - الجعبيري, فرحات‏ بن علي (كلية الآداب والعلوم الإنسانية, 1985)
Keywords: Foi -- Traité

البعد الحضاري للعقيدة الإباضية - الجعبيري, فرحات‏ بن علي (جامعة السلطان قابوس, 1987)
Keywords: Foi -- Traité